The Influence of Adolescent Resilience on Premarital Sexual Behavior - Hasim Asyari; Lisna Anisa Fitriana; Marsono; Kayubi (Jurnal Penelitian Pendidikan IPA, 2025)
Adolescent resilience to premarital sexual behavior refers to the ability of individuals (adolescents) to face and overcome the pressure of premarital sexual behavior in everyday life in a healthy and productive way, namely the ability to adapt to situations by providing responses to improve themselves. Adolescents' permissive attitude towards premarital sexual behavior is associated with low levels of reproductive health knowledge, higher exposure to pornographic media, strong negative group influences, weak parental roles, low religious beliefs and negative environmental influences. This study aims to analyze and explain the relationship between the characteristics of D3 nursing students in Indramayu Regency, internal and external factors, and adolescent resilience to premarital sexual behavior, and to identify the most dominant types of variables. This type of research is an explanatory study with a cross-sectional approach. The respondents were D3 nursing students at both universities in Indramayu Regency totaling 175 respondents. Data were collected using a survey instrument. Data analysis: The analytical approach to this study used univariate techniques, bivariate techniques using the chi-square test, and multivariate techniques using multiple logistic regression tests. This study shows intermediate results, in the univariate test of survey recapitulation of 175 respondents, the majority are: female 140 people (80%), have studied MK Kep. Maternity 113 people (64.6%), live with parents 120 people (68.6%), have high low resilience levels 88 people (50.3%), have good knowledge 119 people (68%), have a permissive attitude 75 people (42.9%), have a strong understanding of religious norms 107 people (61.1%), strong role of parents 118 people (67.4%), positive role of peers 126 people (72%), positive influence of pornographic media 104 people (59.4%) and positive environmental influence 117 people (66.9%)